군인들의 계급에 따른 구강건강관리 실태조사 - 유자혜; Ja Hea Yoo; 김정희; Jung Hee Kim (Han'guk Ch'iwisaeng Hakhoe chi, 2013)
Objectives: The purpose of this study was to perform researches and analysis on the use of dental institutions, oral health behavior, the actual conditions of oral health care, and the oral health knowledge according to the rank of soldiers and officers and then to provide the basic data for the contents development of an oral health education to the military. Methods: The subjects in this study were 380 soldiers serving in Gyeonggi, Gangwon and Chungchong provinces. Results: In terms of the use of dental institutions, the soldiers visit the dental clinics most(56.5%), and the officers visit the military dental clinics most(52.7%)(p<0.05). In the oral health behavior, the most of the soldiers(46.7%) and the officers(58.1%) answer that they thought to be in good oral health. Regarding the actual conditions of oral health care, it is investigated that the most of the soldiers brush their teeth twice a day(46.7%) and the officers three times a day(58.1%). With the oral health knowledge, the officers get a point of 2.89±1.36, which is higher than the soldiers`(2.47±1.27), and the person who have an experience to take an oral health education, getting a point of 2.83±1.22, have higher level of the knowledge than the unexperienced with 2.48±1.31(p<0.5). Conclusions: It is thought to be necessary to provide the military camps with an oral health education and to develop the contents of an oral health education customized to them.